Land-Use Dynamics and Water Quality in Andean Basins (2023)
Conventional agricultural practices, such as the use of agrochemicals, implementation of monocultures, and the expansion of crops in strategic ecosystems, have significant impacts in Andean basins, directly increasing nutrient inputs to waterways, and contributing to ecological fragility and socioeconomic vulnerability. This complex dynamic is related to land-use change and production activities that affect the provision of hydrological ecosystem services. This study presents an integrated analysis of socioecological interactions related to water quality in the Las Piedras River basin (LPRB), a water supply basin located in the Andean region of southwestern Colombia. The analysis was conducted over a five-year monitoring period to assess the spatiotemporal variation and correlation of water quality between streams and agricultural runoff water within the LPRB. Furthermore, water quality indices were calculated based on physicochemical and biological parameters to evaluate the impact of land-use/land-cover changes and agricultural activities within the basin. Results demonstrate that different types of actors, productive logics, mechanisms of use, and access to water within the basin affect water quality and uncertainty for water management, while facing socioecological conflicts between actors.